CD80 cytoplasmic domain controls localization of CD28, CTLA-4, and protein kinase Ctheta in the immunological synapse. - Tseng, S; Liu, M; Dustin, M (2005)
The binding of costimulatory ligand CD80 to CD28 or CTLA-4 on T cells plays an important role in the regulation of the T cell response. We have examined the role of the cytoplasmic domain of CD80 in murine T cell costimulation and its organization in the immunological synapse (IS). Removal of CD80 cytoplasmic tail decreased its effectiveness in costimulating T cell proliferative response and early IL-2 production in response to agonist MHC-peptide complexes. Immunofluorescent study showed a decreased tailless CD80 accumulation in the IS of naive T cells. The two forms of CD80 accumulated differently at the IS; the tailless CD80 was colocalized with the TCR whereas the full-length CD80 was segregated from the TCR. In addition, we showed that CD80, CD28, and protein kinase Ctheta colocalized in the presence or absence of the CD80 cytoplasmic tail. Thus, the cytoplasmic tail of CD80 regulates its spatial localization at the IS and that of its receptors and T cell signaling molecules such as protein kinase Ctheta, and thereby facilitates full T cell activation.